STRATEGI KOMUNIKASI PEMASARAN DALAM MENARIK MINAT CUSTOMER DENGAN APLIKASI GOSEH DELIVERY TANAH KARO‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ - Hamonangan, Yogi Triyuda; Azhar, Anang Anas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to explore the benefits and advantages obtained by stalls by using the Goseh application. The research method used is qualitative, which prioritizes understanding of phenomena that occur through observation and data collection using various methods. This research involved several stalls in Karo District that have used the Goseh application as a means of marketing and selling food and beverages. The results of the study show that the Goseh application provides many benefits to stalls, such as increasing popularity and income. In addition, people also don't need to leave the house to buy food, because they can order through the Goseh application and wait for the order to be delivered to their house. Goseh users are not only limited to people in Karo Regency, but also from outside the city, province, and even abroad who want to pay attention to their loved ones at home by sending their favorite food or drink online. The Goseh application also helps stalls in promoting the stall through the application itself. In addition, Goseh application users can also view the shop's promotional posts via Goseh's official Instagram account and the shop. In this case, promotion can be more effective because it can reach more people, especially social media users. In conclusion, the Goseh application is an effective alternative for stalls in increasing their popularity and income, as well as making it easier for people to order food and drinks from stalls. Apart from that, this application also provides other benefits, such as making it easier to deliver food and drinks to loved ones in their hometown.